Defect-Anchored Dipole Molecules Induce Surface Polarization Facilitating High-Performance Inverted Perovskite Solar Cells - Pan, Weichun; Wu, Jihuai; Pan, Jiexi; Wei, Shanyue; Tan, Lina; Li, Wenjing; Wang, Deng; Liu, Xuping; Xie, Yiming; Lin, Jianming; Lan, Zhang (Nano-Micro Letters, 2026)
The improvement in efficiency and stability of inverted perovskite solar cells (PSCs) is primarily constrained by the charge-carrier and energy losses at the interface of perovskite active layer/charge-carrier transport layers. Herein, a kind of dipolar molecule, 4-aminocyclohexanone hydrochloride (ACHCl), is introduced to the surface of perovskite films in PSCs with p-i-n structure. This surface modification ingeniously utilizes the surface defects of perovskite films to anchor the dipolar molecule, thus inducing surface polarization, which not only effectively reduces interfacial defects but also optimizes the energy-level alignment between the interfaces. Specifically, the carbonyl group and chloride ion on ACHCl anchors on the uncoordinated lead ion defects and fills in the halide vacancies on perovskite surface, respectively, which effectively alleviates the trap-state density, thereby reducing the carrier losses caused by defect-assisted recombination at the interface of perovskite layer/hole transport layer. Meanwhile, the anchoring effect of ACHCl facilitates the formation of a relatively ordered cation-dipole layer and induces surface polarization, resulting in more favorable energy-level alignment and enhanced charge-carrier extraction, ultimately reducing interfacial energy losses. Consequently, the effective reduction in interfacial losses facilitates the ACHCl-modified devices to achieve a power conversion efficiency of 26.12% and improved stability. Highlights: 1 The carbonyl group and chloride ion of 4-aminocyclohexanone hydrochloride (ACHCl) can synergistically passivate surface defects in the perovskite, thereby mitigating the defect-assisted recombination. 2 The ACH+ cations can anchor to positively charged surface defects through the carbonyl group, forming a cationic dipole layer. 3 The formation of an ACH+ cationic dipole layer induces surface polarization, which promotes favorable energy-level alignment and reduces interfacial energy losses.